Queen Red Riding Hood's guide to royalty - Colfer, Chris (London: Little, Brown Books for Young Readers, 2015)
"Dearest reader, we presume you have acquired this magnificent guide because you are either royal, or might one day become royal after narrowly escaping Death by Wolf. Read the pages within for boundless wisdom regarding royal style and advice on how to handle one's subjects (remember: Peasants Are Like Pets). We wish you a long and successful reign (provided you are not an enemy of our kingdom), Queen Red Riding Hood"--Publisher's description
Keywords: Humorous fiction